USE OF TRADEMARK CERTIFICATES AS COLLATERAL IN DOING CREDIT WITH BANKING: PENGGUNAAN SERTIPIKAT MEREK SEBAGAI JAMINAN DALAM MELAKUKAN KREDIT DENGAN PERBANKAN - Tegar Rastratama; Brian Amy Prastyo (SOSIOEDUKASI, 2023)
Intellectual Property Rights are a form of protection for everyone who has creative ideas by creating works. One form of Intellectual Property Rights is Trademark Rights which is a sign given to an item to differentiate it from other goods and has economic value so that it can be used as collateral in making credit with financial institutions. The goal of this article is to examine the use of brand certificates as collateral in banking credit transactions. This analysis was carried out using normative juridical methods. The results of this analysis say that the Mark is part of the Intellectual Property which can be used as collateral by using a certificate as proof of ownership and collateral object.